Dinamika Media Massa dalam Politik Turki dan Peranannya terhadap Konstruksi Wacana Keislaman Turki Kontemporer - Rozi, Ahmad Fahrur; Nurwahidin, Nurwahidin; Muttaqin, Mohammad Izdiyan (Indonesia Center for Middle East Studies, 2024)
This article discusses Türkiye's relationship with the mass media and the role of the press in Islamic discourse. This article departs from the press freedom crisis in Türkiye and the increasing Islamic discourse in contemporary Turkish national media. The author uses the normative function theory of the press and media theory and discourse construction as analytical tools. This article finds that from the perspective of the normative function of the press, the media in Turkey tends to be dominated by an authoritarian system. However, there are a few that adopt a system of social responsibility. Meanwhile, in the context of the media's role in Islamic discourse in Turkey from the perspective of media and discourse construction, the Turkish media signing process tends to be dominated by the juxtaposition of Islamic language and national aspects. In framing, the media raises the discourse of Türkiye's existence in the Islamic world. The image resulting from the signing and framing process is oriented towards national interest and Islam or Turkish Muslim campaigns on the local and global stage.